Structural diversity in de novo cyclic peptide ligands from genetically encoded library technologies. Issue 1 (28th October 2020) - McAllister, Tom E.; Coleman, Oliver D.; Roper, Grace; Kawamura, Akane
Abstract: Cyclic peptides discovered by genetically encoded library technologies have emerged as a class of promising molecules in chemical biology and drug discovery. Here we review the cyclic peptides identified through these techniques reported in the period 2015 to 2019, with a particular focus on the three‐dimensional structures that peptides adopt when binding to their targets. A range of different structures have been revealed through co‐crystal structures, highlighting how versatile and adaptable these molecules are in binding to diverse protein targets, such as enzymes and receptors, or challenging shallow surfaces involved in protein‐protein interfaces. Analysis of the properties of the peptides reported shows some interesting trends, with further insight for those with structural information suggestive that larger peptides are more likely to adopt secondary structure. We highlight examples where co‐crystal structures have informed the key interactions that promote high affinity and selectivity of cyclic peptides against their targets, identified novel inhibitor binding sites, and provided new insights into the biology of their targets. The structure‐guided modifications have also aided the design of cyclic peptides with improved activity and physicochemical properties. These examples highlight the importance of crystallography in future cyclic peptide drug discovery initiatives. Abstract :